Primary school student’s mental wellbeing at schools considering the current situation in Afghanistan - Delju, Zulaikha (International Journal Administration, Business & Organization, 2024)
This study investigates the mental wellbeing of children in primary school in Afghanistan during periods of political instability, specifically focusing on the Taliban's takeover of power in 2021. The study addresses the complex obstacles encountered by children, such as gender-based limitations on education, financial difficulties resulting in child labor, restrictions on personal independence, and changes in educational objectives, through the use of qualitative interviews conducted with teachers and students from different regions. The findings indicate significant impacts on the mental well-being of students, characterized by gender inequalities, financial difficulties, and limited liberties. Teachers also face obstacles such as evolving rules and financial hardships, which can impact their mental health. The evaluation also emphasizes the lack of supportive programs and healthcare services in Afghan schools. This research offers valuable perspectives on the experiences of students and instructors, which can help address the mental health crisis affecting primary school children in Afghanistan.